Correlation of energy intake and availability with aerobic endurance performance - Farrah Lula Klarissa Hendroyono; Muchamad Rizky Sentani; Isti Kumalasari; Delita Septia Rosdiana (Lambung Mangkurat University, 2026)
Futsal is a high-intensity intermittent sport demanding optimal aerobic endurance and adequate nutritional support, particularly for adolescent athletes during growth. This study aimed to determine the relationship between nutrient intake, energy availability (EA), and aerobic endurance among futsal athletes in Bandung. A total of 47 male athletes aged 13-21 years from Futsal 15 Bandung participated in this cross-sectional study. Data collection included three 24-hour food recalls for dietary intake, anthropometric measurements, and the Multistage Fitness Test (Beep Test) for estimating VO2 max. Energy availability was calculated by subtracting exercise energy expenditure (EEE) from energy intake, normalized per fat-free mass (FFM). The results showed significant positive correlations between aerobic endurance, VO2 max, and intake levels of energy (p = 0.003, r = 0.427), carbohydrates (p = 0.003, r = 0.427), protein (p = 0.000, r = 0.514), and fluids (p = 0.002, r = 0.446). However, no significant correlation was found between EA (p = 0.700) or fat intake (p = 0.465) and VO2 max. Most athletes had low EA values (< 30 kcal/kg FFM/day), indicating potential nutritional risks. These findings highlight the importance of adequate macronutrient and fluid intake to support aerobic performance and professional nutritional intervention in athlete development programs.